Cancer of the liver and the use of oral contraceptives. Issue 6532 (24th May 1986) - Forman, D; Vincent, T J; Doll, R
Abstract : A case-control study of the use of oral contraceptives was conducted among women certified as having died from cancer of the liver in the period 1979-82 and in the age range 20-44 years. An age matched group of women who died from other causes, not related to use of oral contraceptives, in the same period were used as controls. Information about use of oral contraceptives was obtained from the general practitioners' notes for both cases and controls. Information was obtained for 30 women with histologically confirmed liver cancer, 19 with hepatocellular carcinoma and 11 with cholangiocarcinoma, and for 147 controls. The results were analysed after adjusting for age at diagnosis and year of birth and showed that use of oral contraceptives was associated with a significantly (p less than 0.05) raised relative risk for hepatocellular carcinoma of 3.8 (95% confidence interval 1.0 to 14.6) and use for eight years or more was associated with a significantly (p less than 0.01) increased relative risk of 20.1 (2.3 to 175.7). There were no apparent increases in risk for cholangiocarcinoma. Despite the small number of cases in this study and the methodological problems in assessing use of oral contraceptives from general practitioners' notes, the results were consistent with other similar studies. Although in the United Kingdom primary liver cancer remains an exceptionally rare disease, especially in young women, further research on the role of oral contraceptives is needed in those countries where it is a much more common disease.